SPIRITUALITY. CULTURE. TOURIST AND LOCAL HISTORY ADOLESCENTS' ACTIVITIES - L.V. Petko (Academy of Cognitive and Natural Sciences, 2022)
The article deals problems of spiritual culture o f the person whih is formed in the process of touristic activity.